Strategi Pengembangan Pendidikan Lingkungan Pada Masyarakat Desa Sukawening, Kabupaten Bogor - Nur Hanifah; Zaenal Abidin (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Humans are one of the elements that can give change through their behavior, one of which is environmental change. Environmental education is carried out consciously and repeatedly or continuously with the aim that the community has awareness and concern for the state of natural resources and all its problems. Sukawening Village is one of the villages in the District of Dramaga which is a village that has major environmental problems regarding waste. This paper aims to examine the activities of environmental education in Sukawening Village and the problems that constrain the implementation of the environmental education program. The author's focus on this activity is the strategy of developing environmental education in Sukawening Village as a reference for the general public, and the village government in particular in overcoming environmental problems in Sukawening Village in order to create a clean and healthy environment.The approach used in this activity includes a qualitative method (SWOT analyze) for reviewing strategies for developing environmental education. Data collection was obtained through interviews and field observations. Based on the SWOT approach taken, the main strategy in the development of environmental education for the people of Sukawening Village is based on traditional wisdom and focus on improving community skills in local resource management. One of the recommendations given by the author is to improve environmental education in Sukawening Village, one of which is that environmental education must be a priority program for the Sukawening village government so that waste problems can be properly addressed and can increase public awareness in protecting the environment. Keywords: enviromental education, garbage, local wisdom, Sukawening villager